ZAD-Domain Is Essential for Nuclear Localization of Insulator Proteins in Drosophila melanogaster - Zolotarev, N.A. (Acta Naturae, 2016)
Many arthropod zinc-finger transcription factors contain a N-terminal domain called ZAD (Zinc-finger Associated Domain), which consists of four cysteines coordinating a single zinc ion. Dimerization ability has been shown for several ZAD-domains. The functional role of this domain is poorly understood. In this paper, we demonstrate that a point mutation within the ZAD-domain of the Zw5 insulator protein disrupts its nuclear localization without affecting its dimerization ability. The importance of the ZAD-domain for nuclear localization has also been shown for the Pita and Grauzone proteins. Therefore, one of the ZAD-domain functions is control of the nuclear localization of transcription factors.